TRW - "Dyer, Davis" (Boston, 1998)
Widely recognized as one of the best run high-tech companies in the world, TRW has helped shape the major industries of today: automotive, aerospace, and information technology. In this revealing account of the firm's pioneering role in long-range planning, large-scale project management, systems engineering, organizational development, and progressive human relations policies, TRW emerges as a resourceful and well-positioned player in the American industrial landscape. The history of TRW's rapid growth, broad diversification, and subsequent restructuring around core businesses provides valuable insights into the evolution of the strategy, structure and management in the modern corporate era.
Keywords: "TRW, Inc.-History"